(untitled) (Agricultural Engineering, 2020)
The paper presents the impact of the initial processing, cultivar, and storage time on the physico-chemical quality of freeze-dried crisps. Sweet pepper after initial washing and crushing was subjected to further four combinations of the initial processing. The first combination included freezing, the second one blanching in 98°C and 2-minutes time, the third one -dehydration in 2% solution of ascorbic acid and the fourth one -dehydration in 2% solution of sodium chloride. Both types of dehydration were carried out in 70°C for 20 minutes with a 1:4 participation of raw material to osmotic solution. Blanched and dehydrated raw materials were subjected to freezing in -18°C for 24 hours. After the completed process of freezing, the samples were moved to a freezer-drier and were dried by sublimation in -18°C and the reduced pressure of 63 Pa. Based on the research analyses a significant variability of physico-chemical properties of the obtained freeze-dried sweet pepper with regard to a cultivar, processing type and storage time were reported. Freeze-dried yellow sweet pepper was the most similar to the fresh raw material. It was dehydrated in the ascorbic acid solution. The storage time considerably influenced the reduction of the quality properties of sweet pepper crisps.